Profile of Arthrogryposis Multiplex Congenita (AMC) patients on surgery treatment at single centered study in orthopaedic hospital and a brief review - Hendra Cahya Kumara; Anung Budi Satriadi; Saddalqous (Journal of International Surgery and Clinical Medicine, 2022)
Introduction: Arthrogryposis multiplex congenita (AMC) is a complex abnormal condition characterized by multiple congenital contractures in the body's joints. Although this condition is not progressive, if not treated properly, it will increase the degree of disability in children. There are two types of AMC. The most common type of AMC is amyoplasia. The second type is distal arthrogryposis (DA), a genetically inherited type characterized by congenital contractures in multiple joints and no neurologic or muscular abnormalities. The incidence of AMC 1:3000 births with clubfeet and congenital hip dislocation is the most common. In this retrospective study, the authors described the profile of AMC patients who underwent surgery at our center with the approach and management. Method: The study design was a descriptive retrospective. The population of this study is all AMC patients who underwent surgery at the orthopedic hospital of Prof. Soeharso Surakarta, Indonesia. We used the total sampling technique who underwent surgery in the 2018-2021 period. Result: In this study, we got eleven AMC patients who underwent surgery. Distribution based on sex found six boys and five girls. Half of the patients underwent surgery under the age of three years, while the other half underwent surgery after the age of five. The presence of patients who are consulted at an older age indicates a lack of public literacy about the abnormal condition of AMC or a lack of concern for the condition. Almost all AMC patients who undergo surgery are in the lower extremities. Conclusion: Rehabilitation plays a very important role in improving the quality of life for AMC patients. A multidisciplinary approach is needed in the treatment of AMC patients. Surgery is performed if stretching and external support splinting/casting cannot achieve functional ROM and repair the deformity.